2020
DOI: 10.1590/s0100-83582020380100069
|View full text |Cite
|
Sign up to set email alerts
|

Weed control of glufosinate, oxyfluorfen, and paraquat as affected by the application time of day

Abstract: control of glufosinate, oxyfluorfen, and paraquat as affected by the application time of day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In addition to these aspects, the climatic condition can also influence the determination of a synergistic, antagonistic, or additive effect in the mixing of a herbicide with foliar fertilizer; in dry climate conditions and lower relative humidity, as observed in our experiment, the cuticles of soybean plants tend to become thicker and, thus, reduce the possibilities of synergism in the combination of herbicides and foliar fertilizers (MONTGOMERY et al 2017, ALIVERDI et al 2020. HECKMAN et al (1999) have observed that the phytotoxicity in soybeans inherent in the application of post-emergence herbicides (acifluorfen, chlorimuron, imazethapyr, and bentazon) associated with manganese sulfate were not different from the herbicides applied without manganese sulfate.…”
Section: Resultsmentioning
confidence: 74%
“…In addition to these aspects, the climatic condition can also influence the determination of a synergistic, antagonistic, or additive effect in the mixing of a herbicide with foliar fertilizer; in dry climate conditions and lower relative humidity, as observed in our experiment, the cuticles of soybean plants tend to become thicker and, thus, reduce the possibilities of synergism in the combination of herbicides and foliar fertilizers (MONTGOMERY et al 2017, ALIVERDI et al 2020. HECKMAN et al (1999) have observed that the phytotoxicity in soybeans inherent in the application of post-emergence herbicides (acifluorfen, chlorimuron, imazethapyr, and bentazon) associated with manganese sulfate were not different from the herbicides applied without manganese sulfate.…”
Section: Resultsmentioning
confidence: 74%
“…We hypothesize that the plants' ability to recover enzyme activity comes from de novo synthesis of GS, given that glufosinate was not able to completely control these plants when treatment occurred at dusk. This is particularly interesting because GS activity is known to be lower in the dark compared to the light in both A. palmeri (Figure 3) and other plant species [23]. In addition, GS2 is highly expressed in the leaves while GS1 is more abundant in roots (Figure 2).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, glufosinate performance depends on the time of day at which the herbicide is sprayed in the field. Several papers have reported the time-of-day effect on glufosinate efficacy for several weed species [21,22,23]. One common observation is that glufosinate performance was lower when the herbicide was applied at either dusk or dawn compared to midday applications.…”
Section: Introductionmentioning
confidence: 99%